198k views
3 votes
I WILL GIVE BRAINLEY TO THE MOST CORRECT AND FIRST ANSWER PLUS A LOT OF POINTSS!! PLEASE HELP ME ASAPPPP!

-2 + (-6y) + 5 y - 8y y=4
4x + 5 - 5x x=12
4x + 2y - x - 8 x =1 y =5
-3 + 9 -(-4y) + 5x x =1 y =-5
-8 - 4x + y - 6x x =-9 y =9
7x + 1 - y - 3x - (-9) x =7 y =-6
5x + (-y) + 8 -6x + 9y x =4 y =-2
7 - x + 4y - 6x -3y x =-1 y =8
-x - (-y) + (-x) - y + 5 x =-3 y =-6

1 Answer

5 votes
Answers in order:
-38
-7
5
-9
91
44
-16
22
11

Step by step explanation:
I used a calculator
User Zhenglei
by
4.7k points